Summary Report Of The 2002 Survey Cruise For Cobalt-Rich Manganese Crust In The EEZ Of The Marshall Islands - Yoshitaka Hosoi (International Marine Minerals Society, 2003)
The survey of the cobalt-rich crust of the Republic of the Marshall Islands was carried out in 1996 and 1998, as the cooperative study project between Japan and SOPAC member countries, and at the thirteen seamounts, seafloor topographic maps and acoustic reflection intensity distribution images by MBES were obtained, and the collection of samples by dredging was conducted. On the basis of the previous results, three seamounts, MS01, MS11 and MS12 were selected for the 2002 year survey, and drilling by BMS (deep sea boring system) was conducted there, to understand the occurrence of cobalt-rich crust. At the same time, environmental survey was carried out to make clear the environmental characteristics of the area. The summary of the survey will be reported.